Propionate‐producing engineered probiotics ameliorated murine ulcerative colitis by restoring anti‐inflammatory macrophage via the GPR43/HDAC1/IL‐10 axis - Guangbo Kang; Xiaoli Wang; Mengxue Gao; Lina Wang; Zelin Feng; Shuxian Meng; Jiahao Wu; Zhixin Zhu; Xinran Gao; Xiaocang Cao; He Huang (Wiley, 2024)
Abstract Inflammatory bowel disease (IBD) is a chronic and unspecific inflammatory disorder of the gastrointestinal tract, and current treatment options often fail to maintain long‐term remission. Studies have shown that propionate level is reduced in fecal samples from patients with IBD. Propionate can ameliorate IBD through intestinal epithelial cells and immune regulation, but its effects on the inflammatory microenvironment and macrophage differentiation have not been widely studied. To address this, we constructed an engineered propionate‐producing probiotic (EcNP3) to achieve sustained restoration of propionate levels in the gut and increase its bioavailability. DSS‐induced experimental intestinal inflammation model was used to evaluate the effect of EcNP3 on improving the intestinal mucosal barrier and increasing the proportion of anti‐inflammatory macrophages. It was found that EcNP3 exhibited a restorative effect on the depletion of peritoneal anti‐inflammatory macrophages (F4/80hiCD11bhi) and significantly improved the expression level of IL‐10. Simultaneously, the expression of IL‐1β, IL‐6, and CXCL1 was downregulated while inhibiting apoptosis of tissue‐resident macrophages ex vivo. Further investigation revealed that EcNP3 regulates IL‐10 expression through G protein‐coupled receptor 43 and histone deacetylase. Furthermore, EcNP3 significantly inhibited the protein expression of HDAC1 and promoted the histone acetylation level of cells. Finally, EcNP3 significantly improved DSS‐induced colitis in mice by increasing mucus production and reducing inflammatory infiltration. Our results suggest that the engineered live biotherapeutic product EcNP3 is a safe and potently efficacious treatment for IBD, which defines a novel strategy in IBD therapy through macrophage IL‐10 signaling.